2017
DOI: 10.1177/0271678x17725417
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic endfoot Ca2+ correlates with parenchymal vessel responses during 4-AP induced epilepsy: An in vivo two-photon lifetime microscopy study

Abstract: Neurovascular coupling (NVC) underlying the local increase in blood flow during neural activity forms the basis of functional brain imaging and is altered in epilepsy. Because astrocytic calcium (Ca) signaling is involved in NVC, this study investigates the role of this pathway in epilepsy. Here, we exploit 4-AP induced epileptic events to show that absolute Ca concentration in cortical astrocyte endfeet in vivo correlates with the diameter of precapillary arterioles during neural activity. We simultaneously m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
(55 reference statements)
5
23
0
Order By: Relevance
“…In this study, we aimed to quantify the hemodynamic properties of and modulatory role of exercise on cerebral capillaries in AD due to the important role of microcirculation in cognitive health (Østergaard et al, 2016;Erdener et al, 2017;Zhang et al, 2017;Hernández et al, 2019). Exploiting awake microscopic vascular imaging and a transgenic mouse model of AD, we found that in this model (APP-PS1), AD is associated with hemodynamic disruption in capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to quantify the hemodynamic properties of and modulatory role of exercise on cerebral capillaries in AD due to the important role of microcirculation in cognitive health (Østergaard et al, 2016;Erdener et al, 2017;Zhang et al, 2017;Hernández et al, 2019). Exploiting awake microscopic vascular imaging and a transgenic mouse model of AD, we found that in this model (APP-PS1), AD is associated with hemodynamic disruption in capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are located close to blood vessels. The endfeet of astrocytes surround the vessels and contribute to neurovascular coupling (NVC) [ 20 ]. Astrocytic calcium levels are increased in the activated form.…”
Section: Epilepsymentioning
confidence: 99%
“…NVC is the process that links localized neuronal activity in the brain to vasodilation of proximate PAs so as to ensure adequate delivering of oxygen and nutrients to metabolically active regions of the central nervous system. A key component of NVC is the K IR ‐dependent SMC hyperpolarization and vasodilation that results from modest increases in [K + ] o within the perivascular space . In isolated PAs, raising [K + ] o from 3 mM to 8 mM hyperpolarizes the SM V m to near the new E K of −76 mV, causing near maximum vasodilation by decreasing Ca 2+ influx .…”
Section: Impact Of Small Vessel Pathologies On the Interplay Between mentioning
confidence: 99%